Cross-Border Mobility : Women, Work and Malay Identity in Indonesia. - Mee, Wendy (New Mobilities in Asia Ser., 2019)
This book offers a fresh perspective on the association between mobility and the ethnocultural category Malay. In so doing, it raises new research questions relevant to the study of Indonesian women's socioeconomic mobility more generally. Based on fieldwork in Sambas, a border region of Indonesia, the book documents the ethnocultural consequences of Sambas Malay women's highly mobile working lives. The book also extends our appreciation of the significance of territorial borders in women's working lives. In this study, women's border location not only facilitates cross-border pathways of international labour migration and trade, but also generates feelings of peripherality that inform women's imaginative construction of other, non-territorial borders to be crossed. Shaped by social class, gender, and the economic and cultural possibilities of political decentralization, the study identifies three borderscopes that orient women's work-related mobility in different directions and bring with them diverse outcomes for the ethnocultural category 'Sambas Malay'.